Implementation Of The Concept Of Religious Moderation In Islamic Religious Education For Students - Rasyidatun Mahdiyyah; Jasminto Jasminto (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to explore the concept of religious moderation among students, describe the implementation of Islamic religious education, and analyze the integration of religious moderation principles within Islamic education at SD Negeri Grogol 2 Diwek Jombang. It is a field study employing a qualitative descriptive approach. Data sources were selected through purposive sampling, followed by snowball sampling to obtain broader and deeper insights. Data collection was conducted through classroom observations, in-depth interviews, and document analysis. The data analysis technique used was descriptive analysis. The research findings indicate that the application of religious moderation concepts has been effectively implemented, as reflected in their consistent integration into daily practices. This is further supported by extracurricular and social programs that enhance children’s understanding of religious moderation, particularly in how they coexist within multicultural environments. Islamic education is delivered through classroom instruction and is supported by diniyah and mulok learning programs. The principle of religious moderation is embedded in Islamic education through content that emphasizes moderation, as conveyed by teachers. It also includes how students apply religious knowledge in diverse social settings—across differences of race, ethnicity, and religion.